2021
DOI: 10.1021/acs.organomet.1c00333
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of End-Functionalized Poly(norbornenes) and Poly(ethylidene norbornenes) Using a Pd(II) Catalyst in Combination with Chain Transfer Agents

Abstract: Synthesis of end-functionalized poly­(norbornenes) (PNBs) and poly­(ethylidenenorbornenes) (PENBs) were prepared using the palladium catalyst t Bu3PPdMeCl/NaBArf in combination with the chain transfer agents (CTAs) 4-penten-1-ol and 10-undecenal. These CTAs produce polymers end-capped with −OH and −CHO groups, respectively, in high yields with M n values in the range of 6–17K, depending on the CTA:monomer molar ratio. End-functionalized PNBs and PENBs with precisely controlled M n values and very narrow molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Furthermore, palladium-catalyzed alkyne oligomerization often leads to stereoisomer mixtures or cyclic oligomerization. ,,,, Consequently, we decided to explore well-defined monodentate phosphine palladium catalysts for the polymerization of functionalized terminal acetylenes. Such bulky monophosphine palladium complexes play an important role in cross-coupling methodology and polymer synthesis. , Specifically attractive are Buchwald’s bulky diarylphosphine ligands, in which weak palladium–arene interactions between the metal center and the ligand aromatic ring may result in better catalyst stability while allowing access of the substrate to the catalyst “vacant site”. We report here the preparation of a new Pd complex 1 ligated with the bulky diarylphosphine (tBuXPhos), which polymerizes a wide scope of terminal acetylenes affording head-to-tail and cis–transoidal polymers (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, palladium-catalyzed alkyne oligomerization often leads to stereoisomer mixtures or cyclic oligomerization. ,,,, Consequently, we decided to explore well-defined monodentate phosphine palladium catalysts for the polymerization of functionalized terminal acetylenes. Such bulky monophosphine palladium complexes play an important role in cross-coupling methodology and polymer synthesis. , Specifically attractive are Buchwald’s bulky diarylphosphine ligands, in which weak palladium–arene interactions between the metal center and the ligand aromatic ring may result in better catalyst stability while allowing access of the substrate to the catalyst “vacant site”. We report here the preparation of a new Pd complex 1 ligated with the bulky diarylphosphine (tBuXPhos), which polymerizes a wide scope of terminal acetylenes affording head-to-tail and cis–transoidal polymers (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…The M n, NMR of most low-molecular-weight samples agree with the corresponding M n, GPC (see Table S1 for more details), confirming β-H elimination and chain transfer as the chain termination pathway. There have been several studies of Ni/Pd-catalyzed NBE or NBE derivative copolymerizations, in which ethylene, ,,, α-olefin, , 4-penten-1-ol, or 10-undecenal plays the role of chain transfer agent (CTA). Meanwhile, these Ni/Pd catalysts show either no activity or no oligomerization capability when used in reactions with ethylene, α-olefin, or functionalized α-olefins.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13][14][15][16] Based on these advantages, aldehyde end-capped polymers are promising for the applications of drug delivery, diagnosis, surface modification and construction of supramolecular architectures. [17][18][19] For instance, Haddleton et al demonstrated the synthesis of aldehyde end-capped methacrylic polymers by living radical polymerization for protein conjugation. 13 Brookhart et al developed a strategy to prepare aldehyde endfunctionalized polyolefins using an unsaturated alcohol as the chain-transfer agent (CTA).…”
Section: Introductionmentioning
confidence: 99%